Education Based on Innovation and Creativity in Improving the Competitiveness of Micro, Small and Medium Enterprises - Abidin, Zaenal; Kuswanto, Kuswanto; Ismawati, Sri Ida; Baros, Vionita; Nilfatri, Nilfatri (Zabags International Journal of Engagement, 2023)
The purpose of this study is to determine the level of innovation and creativity of micro, small and medium enterprises in increasing income. The challenge that will be faced is in the form of economic activities that depend on global competition that is free and open so that only strong business actors will survive. Globalization has caused the world economy to experience a paradigm shift into a knowledge and creativity-based economy. This activity aims to conduct education based on innovation and creativity as an answer to the impact that globalization has brought. Implementation of this activity using the survey method. Based on the survey results, Micro, Small and Medium Enterprises in Lambur Village are still not ready to face the challenges presented by Globalization. Therefore, Community Service Program STIE Syari'ah Al-Mujaddid Group 1 seeks to increase the competitiveness of Micro, Small and Medium Enterprises based on innovation and creativity in the form of legalizing business licenses, and innovating products through upgrading packaging and adding flavor variants to products. To realize this, this community service activity uses a method which consists of three stages, namely the preparation stage, the implementation stage and the evaluation stage. The results of this activity are that it can have an impact on changing the products of Micro, Small and Medium Enterprises in Lambur Village, Muara Sabak Timur District, Tanjung Jabung Timur Regency.